Expanding the concept of social behavior to interspecific interactions - Oliveira, Rui F. (2022)
In pretty much any species, an individual's survival and reproduction depends crucially on the outcome of interactions with other individuals. Key interactions may take place between individuals of the same species but also between individuals belonging to different species. However, the most accepted definition of social behavior only considers interactions between conspecifics. Here, we argue that the distinction between intra- and interspecific interactions is largely artificial and hinders the integration of the historically separately developed concepts. At the ultimate level, given that the ecological landscape of organisms is composed both by interactions with conspecifics and with heterospecifics, and both types of interactions may have evolutionary consequences. Although intraspecific interactions usually have a higher impact in fitness because in most species interactions relevant for reproduction (mating, parenting) exclusively involve conspecifics, and interactions relevant for survival are more probable between conspecifics because they share the same ecological niche, hence competing for the same resources (e.g., food, shelter), there are notable exceptions in both fitness components (e.g., heterospecific mating in parthenogenic all-female species; heterospecific brood parasitism; heterospecific aggression in sympatric species that compete for shared resources). At the proximate level, behaviors and cognitive decision-making rules used to interact with other organisms may be shared between intra- and interspecific interactions, and the mechanistic differences between conspecific social behaviors used in distinct functional domains, such as mating, aggression, or parenting, can be more expressive than those found within the same functional domain between conspecific and heterospecific behavior. Therefore, there are neither fundamental conceptual (ultimate) reasons, nor key differences in mechanisms underlying behaviors involved in conspecific vs. heterospecific interactions that support the exclusion of interspecific interactions from the conceptual framework of social behavior